Invasive assessment of aortic stenosis in contemporary practice - Brito, João; Raposo, Luís; Teles, Rui Campante (Frontiers in Cardiovascular Medicine, 2022)
The authors review the current role of cardiac catheterization in the characterization of aortic stenosis, its main clinical applications, its pitfalls, and its additional value to the information provided by echocardiography. Discrepancies that may arise between these two modalities are discussed and further explained. Hemodynamic variables besides transvalvular pressure drop are described, and emphasis is given to an integrative approach to aortic stenosis assessment, that includes invasive and noninvasive evaluation.